DRUG FACTORS INFLUENCING ITS USE AMONG UNDERGRADUATE STUDENTS OF A TERTIARY INSTITUTION IN NIGERIA - AREMU, SAAD BOLAKALE (Advances in Social Sciences Research Journal, 2018)
OBJECTIVE: Drug use and abuse have been reported to be one of the main causes of impairment of social competence and performance among students. Also, school drop out, criminal tendencies and poor social interaction have also been reported to be associated with drug abuse among these students. Knowing the Prevalence and patterns of drug use, number of drug use, reason for use, sustainability and duration of drug used as drug factors will help in primary prevention strategy in tertiary institutions in Nigeria and globally. METHODS: A descriptive cross sectional study involving four hundred and forty (440) subjects selected through multistage sampling techniques. All the subjects consented and participated in the study. Self administered socio demographic, WHO students’ drug use and drug factors influencing use questionnaires were administered to the subjects to fill through their class representative. Statistical package for social science (SPSS) 15th editions was used in Data analysis. RESULTS: Four hundred and forty (440) students drawn from 3 faculties of the university participated in the study. One hundred and fifty (150) respondents constituting 34.1% were from faculty of Engineering, one hundred and fifteen (115) respondents constituting 26.1% were from faculty of Education while one hundred and seventy five (175) respondents constituting about 39.8% were from college of Medicine. One hundred and thirteen subjects (25.7%) used one and more of all the 10 drugs examined by the questionnaires. Duration of tobacco use revealed that 40 had used it 5years and above, 15 used it between 3-5years, 4 used it between 6months-1year while 2 tobacco users had 1-3years as duration of usage. The differences was statistically significance (df =4, x2= 12.07, p=0.01). All the 6 cocaine users(1.4%) take 3 other drugs alongside cocaine. The difference was also statistically significant (df= 3, x2= 26.21, p=0.00). Multiple drug use of 3 and more was found to be significant with many of the drugs examined. CONCLUSIONS: Prevalence, patterns and drug factors revealed that psychoactive drug use was found among students of Ahmadu Bello University Zaria like in other institutions of higher learning in Nigeria. Appropriate interventions like health education, social support system, counseling, referral systems, parental supervision and enforcement of necessary laws by regulatory agencies were some of the recommendations to curb the menace in our institutions in Nigeria.